PENGARUH PBB, PAJAK HOTEL, DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN NGANJUK 2020-2022 - Wulandari, Wulandari; Widiawati, Hestin Sri; Sugeng, Sugeng (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The background of this research is that land and building tax revenue does not meet the set targets and the percentage of hotel and restaurant tax revenues will decrease in 2022, while Nganjuk district is one of the areas with the highest percentage of realized APBD spending, namely 71.67 percent (damarinfo.com). This can affect the State Revenue and Expenditure Budget (APBN), both the expenditure budget for the central and regional governments. Therefore the aim of this study was to determine the effect of land and building tax, hotel tax, and restaurant tax on local revenue either partially or simultaneously in Nganjuk Regency. This study uses a quantitative approach. This study uses the subject object and is analyzed using multiple linear regression with SPSS software for windows version 25. The results of the study found that: (1) Land and Building Tax has a significant effect on Regional Original Income. (2) Hotel Tax has no significant effect on Local Own Revenue. (3) Restaurant Tax has a significant effect on Regional Original Income. (4) Simultaneously, land and building taxes, hotel taxes, and restaurant taxes affect local revenue.